1982
DOI: 10.1073/pnas.79.2.386
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of leucine side-chain reorientation in collagen-fibrils by solid-state 2H NMR.

Abstract: We have used 2H quadrupole-echo NMR spectroscopy to study the molecular dynamics of the leucine side chain in collagen fibrils labeled with [2H10]leucine. X-ray crystallographic studies ofleucine and small leucyl-containing peptides and proteins [Benedetti, C. (1977) at 313 nm to establish purity. The percentage incorporation of deuterium (43%) was determined by chemical ionization gas chromatography/mass spectrometry of N-acetylmethyl ester derivatives of the hydrolyzed protein. Radiotracer (3H and 14C) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
135
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 10 publications
12
135
0
Order By: Relevance
“…, 1 2 = +60 ) and solid-state NMR results indicate that there is rapid interconversion between them (Batchelder et al, 1982;Colnago et al, 1987), though the motion may be more complex than described by this simple two-site jump model (Yang et al, 1998). Dunbrack & Karplus (1993) observed that of 19 leucine residues whose side-chain conformations they had been trying to predict in six proteins, nine of them could have had wrong dihedral angles in the published structures owing to errors in map interpretation arising from positional degeneracy.…”
Section: Comparison With Data From Peptides and Atomic Resolution Strmentioning
confidence: 98%
“…, 1 2 = +60 ) and solid-state NMR results indicate that there is rapid interconversion between them (Batchelder et al, 1982;Colnago et al, 1987), though the motion may be more complex than described by this simple two-site jump model (Yang et al, 1998). Dunbrack & Karplus (1993) observed that of 19 leucine residues whose side-chain conformations they had been trying to predict in six proteins, nine of them could have had wrong dihedral angles in the published structures owing to errors in map interpretation arising from positional degeneracy.…”
Section: Comparison With Data From Peptides and Atomic Resolution Strmentioning
confidence: 98%
“…2 H NMR has long been used to determine the degree to which amino acid side chain dynamics are sensitive to structural environment, for example, the perturbation of the motion of leucine side chains in collagen fibrils (30), the dynamic impact of polylysine adsorption onto silica and hydroxyapatite surfaces (31), and the dynamics of hydrophobic side chains in membrane-associated proteins (32)(33)(34). Additionally, 13 C-2 H NMR correlation techniques have been used by Reif and coworkers to identify the dynamics of deuterated valine and leucine side chains in uniformly 13 C-labeled micro-crystalline proteins (35,36).…”
mentioning
confidence: 99%
“…Models for the motion of leucine side chains are usually based on the assumption that exchange occurs between a subset of these bond rotational isomers. For example, in a 2 H NMR study of helical collagen fibrils with L-leucine-2 H 10 uniformly incorporated, Batchelder et al (30) assumed exchange of the side chain between two conformers observed to be dominant in leucylpeptide crystal structures: tg þ and g − t, where g þ , g − , and t correspond to the gauche þ, gauche −, and trans rotational isomers of the C α -C β and C β -C γ bonds. The temperature variation of the 2 H line shape was modeled as variation in the rate of exchange between these two conformations of the leucine side chain, assumed to occur with equal a priori populations.…”
mentioning
confidence: 99%
“…Moreover, reported 13 C NMR experiments did not display a sufficient spectral resolution to allow a clear distinction among the different amino acid carbon resonances (9,10). NMR studies using specific residue labeling have given valuable information on dynamics (11)(12)(13). To deduce the backbone conformation, Saitô et al (9) have compared 13 C chemical shifts of fibrillar collagen with those obtained on small triple helical peptides.…”
mentioning
confidence: 99%